Baby Touch Textile / Liza Idris ... [et al.] - Idris, Liza; Mohammed Basar, Norazila; Mohd Idris, Norfaizah; Mohd Badri, Nurdiana (Faculty of Civil Engineering, 2004)
Baby Touch Textile is a company that involves in sells textiles. This company sells variety of textile and also ready made clothes. This company was formed the effort and co-operation of four partners. This company also offers variety choice of textile such as silk, organza, cotton, lace, linen etc. These varieties of textile come from locally and other countries like Asian and European. Our company gets all that type of textile from our supplier which is Takzim Textile.